Desempeño Económico Financiero de los principales Bancos Privados del Ecuador en la última década - Pozo Ortega, Zorey Efat (2024)
The financial analysis of banks is indispensable because it evaluates the economic situation through the structure, evolution of accounts, and key financial indicators; considering that they allow the identification of risks, opportunities, and the bank's capacity to comply with its obligations; thus guaranteeing stability and growth in the financial market. Therefore, it is important to evaluate the economic and financial performance of the main private banks in Ecuador in the last decade. The methodology applied had a mixed approach, with a descriptive and correlational scope. Inductive, deductive, analytical, and synthetic methods were used. The financial analysis was carried out using the CAMEL method, and Pearson's correlation was applied to measure the relationship, concluding with the PEST management tool. The research design is longitudinal, since information from four banks over the last ten years, obtained from the web portal of the Superintendence of Banks of Ecuador, was used to identify the study's variables. The results revealed that Banco Guayaquil stands out in its financial economic efficiency indicators. In addition, a direct relationship was found between ROE and ROA with general management and asset quality. It is concluded that an exhaustive evaluation of the main banks helps to have a complete vision that facilitates meaningful comparisons; in addition, it allows an accurate and fair classification, taking into account key aspects such as economic efficiency, delinquency, and profitability.